Efficacy and effectiveness of artemether-lumefantrine after initial and repeated treatment in children <5 years of age with acute uncomplicated Plasmodium falciparum malaria in rural Tanzania: a randomized trial. - Ngasala, B; Malmberg, M; Carlsson, A; Ferreira, P; Petzold, MG; Blessborn, D; Bergqvist, Y; Gil, J; Premji, Z; Björkman, A; Mårtensson, A (2011)
BACKGROUND: We assessed the efficacy, effectiveness and safety of artemether-lumefantrine, which is the most widely used artemisinin-based combination therapy in Africa, against Plasmodium falciparum malaria during an extended follow-up period after initial and repeated treatment. METHODS: We performed an open-label randomized trial of artemether-lumefantrine with supervised (n=180) and unsupervised intake (n=179) in children <5 years of age with uncomplicated falciparum malaria in rural Tanzania. Recurrent infections between day 14 and day 56 were retreated within the same study arm. Main end points were polymerase chain reaction (PCR)-corrected cure rates by day 56 and day 42 after initial and repeated treatment, respectively, as estimated by survival analysis. RESULTS: The PCR-corrected cure rate after initial treatment was 98.1% (95% confidence interval [CI], 94.2%-99.4%) after supervised and 95.1% (95% CI, 90.7%-98.1%) after unsupervised intake (P=.29). After retreatment of recurrent infections, the cure rates were 92.9% (95% CI, 81.8%-97.3%) and 97.6% (95% CI, 89.3%-98.8%), respectively (P=.58). Reinfections occurred in 46.9% (82 of 175) versus 50.9 % of the patients (relative risk [RR], 0.92 [95% CI, 0.74-1.14]; P=.46) after initial therapy and 32.4% (24 of 74) versus 39.0% (32 of 82) (RR, 0.83 [95% CI, 0.54-1.27]; P=.39) after retreatment. Median blood lumefantrine concentrations in supervised and unsupervised patients on day 7 were 304 versus 194 ng/mL (P<.001) after initial treatment and 253 versus 164 ng/mL (P=.001) after retreatment. Vomiting was the most commonly reported drug-related adverse event (in 1% of patients) after both initial and repeated treatment. CONCLUSIONS: Artemether-lumefantrine was highly efficacious even after unsupervised administration, despite significantly lower lumefantrine concentrations, compared with concentration achieved with supervised intake, and was well-tolerated and safe after initial and repeated treatment. CLINICAL TRIAL REGISTRATION: ISRCTN69189899.